The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.1093/gbe/evac024
|View full text |Cite
|
Sign up to set email alerts
|

High Stability of the Epigenome inDrosophilaInterspecific Hybrids

Abstract: Interspecific hybridization is often seen as a genomic stress that may lead to new gene expression patterns and deregulation of transposable elements (TEs). The understanding of expression changes in hybrids compared to parental species is essential to disentangle their putative role in speciation processes. However, to date we ignore the detailed mechanisms involved in genomic deregulation in hybrids. We studied the ovarian transcriptome and epigenome of the Drosophila buzzatii and Drosophila koepferae specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 96 publications
(198 reference statements)
2
2
0
Order By: Relevance
“…In our study, we performed Nanopore sequencing for seven cactophilic Drosophila species/subspecies. Both genomes of D. buzzatii and D. koepferae had 175 Mb of estimated genome sizes, which is similar with 160 Mb and 169 Mb obtained on previously assemblies (46,61), performed through the combination of short and long reads technologies. Furthermore, we obtained 11,347 and 11,440 fully annotated genes in D. buzzatii and D. koepferae , which is very similar with the previous 10,983 and 11,804 obtained for the same species.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…In our study, we performed Nanopore sequencing for seven cactophilic Drosophila species/subspecies. Both genomes of D. buzzatii and D. koepferae had 175 Mb of estimated genome sizes, which is similar with 160 Mb and 169 Mb obtained on previously assemblies (46,61), performed through the combination of short and long reads technologies. Furthermore, we obtained 11,347 and 11,440 fully annotated genes in D. buzzatii and D. koepferae , which is very similar with the previous 10,983 and 11,804 obtained for the same species.…”
Section: Discussionsupporting
confidence: 84%
“…The resolution of gene annotation for D. arizonae was similar to D. mojavensis subspecies due to the recent (1.5 Mya) divergence between them (43), whereas for D. buzzatii and D. koepferae it was ~23% smaller compared to D. mojavensis, as expected since they are more distant related species (44). Similar amount of genes had been annotated previously in the D. buzzatii (45,46) and D. koepferae (46,40) genomes. Since analysis on HLAU genes is the focus of this study, their efficient annotation is relevant.…”
Section: Genome Assemblies and Gene Annotationsupporting
confidence: 74%
See 1 more Smart Citation
“…Even though we noticed that changes in expression of few specific TE families could be explained by their small RNA amount changes after heat stress, we did not detect this clear association globally, which was in concordance with other studies ( Funikov et al 2015 ; Fast et al 2017 ) and highlighted that other mechanisms could also be involved in this activation. For example, changes in the epigenome affecting TE expression under the genomic stress have been observed previously ( Bodelón et al 2022 ). Specifically, Hsp83 was described to be involved in epigenetic modification ( Tariq et al 2009 ), as well as other changes in the epigenome have been observed after a heat stress ( Arrigo 1983 ; Pauli et al 1992 ).…”
Section: Discussionmentioning
confidence: 54%